SOCIAL PORTRAIT OF A MODERN WORKING OF A STUDENT: A SOCIOLOGICAL ANALYSIS - Zhelnina, E.V; Papchihina, M.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The article presents the results of a sociological study aimed at studying the social characteristics of modern working students. The relevance of the topic of student orientation, choice and interests is explained by the ongoing changes in the values of modern Russian students. This work is aimed at studying the social portrait of a modern working student. The object of the study is the student youth, the subject - a social portrait of a working student, which reflects the interests, values, material opportunities and plans for the future of modern students. The features and characteristics of students who combine study with work are studied. The work also includes the study of employers ' opinions about modern students. It turned out that more boys than girls are going to work in the specialty after graduation. Students combine work with study, first of all, for the sake of additional earnings. Also, students, combining study with work, often do not work in the specialty. Boys earn more than girls by combining work and study. The hypothesis that students on a commercial basis often combine study and work was not confirmed. More than half of the surveyed students who combine study with work are studying on a budget basis.